Kuda Bendi di Kota Payakumbuh Sumatera Barat Sampai Akhir Abad Ke-20 - Fikrul Hanif Sufyan Sufyan (Universitas Airlangga, 2017)
Kuda-bendi (two-wheeled carriage drawn by a horse) has a vital role in the life of Minangkabau society. As a traditional transportation, kuda-bendi took the highest level among other traditional transportation, and represented its users' level. Thus, it is necessary to be discussed, how was the development of kuda-bendi transportation in the 19th until 20th century? What factors which led kuda-bendi transportation being marginalized? What are bendi's coachman strategies in facing the rivalry of modern transportation? And how is the government policy addressing the issue of kuda-bendi problems in the middle of Payakumbuh development?. This research is aimed at framing the strategy which is used by bendi’s coachman and local government in maintaining the existence of kuda-bendi on facing the rapid development of modern transportation. Due to these objectives, the historical method which is implemented in this research consist of collecting the source (heuristic). After heuristic, doing criticism to the discovery resource; interpretation; and historiography. Until the mid of 20th century, kuda-bendi was a transportation for pangreh praja, penghulu, merchant, and rich men in Payakumbuh, defeated the popularity of kerbau-pedati (a carts drawn by buffalo) and horse-load. Since the government of Dutch East Indies introduced model of western transportation to Minangkabau people, especially in Payakumbuh, caused the kuda-bendi's position become marginalized. Recently, Payakumbuh society tends to use transportation, such as public transportation, motor tricycle, rent motorcycle, which take them more quickly to their destination. Some of them try to modernize their selves so they are not disappeared in the modern era.